Mobile application challenges - Kamsan, Siti Zulalina; Mohd Affandi, Nur Iman; Mohd Nazri, Nurul Athirah; Jailani, Nureen Syafiqah; Sundramorthy, Saranya; Rajasakar, Kirthana; Nathan, Shelena Soosay (Penerbit UTHM, 2021)
Over the last ten years or so, mobile devices technology has changed significantly, with these devices and operating systems becoming more sophisticated. These developments have led to a huge variety of mobile applications designed for mobile operating systems. These mobile applications are typically harder to design and build because of several factors such as screen size and limited processing power and so forth. Therefore, it is important to clearly identify the characteristics of mobile application development and the issues and challenges related to it, as well as, the key features that characterize a great mobile application which make them valuable and useful. This paper has reviewed existing literature of the challenge and best practices of mobile application development. This study contributes towards a great understanding of the characteristics of the mobile application development process, examines real challenges faced and explores the best practices that can be effectively applied to improve the development of mobile applications.